Student-staff partnerships at work: epistemic confidence, research-engaged teaching and vocational learning in the transition to higher education. Issue 2 (15th March 2021) - Davis, Charlie; Parmenter, Luke
ABSTRACT: This study adapted a participatory action research (PAR) approach as part of student-staff collaboration aimed at co-producing a research-engaged pedagogy to provide vocational students with access to curricular opportunities to develop their academic capabilities. This article focuses on the co-creation process between seven multidisciplinary higher education (HE) students at different stages in their studies and two academic support staff. The participants immersed themselves in a double-loop inquiry process, researching student perceptions of belonging in their institution to co-produce knowledge to develop a research-based pedagogy. Working with the concept of epistemic injustice, we consider how participation in the inquiry influenced the student participants' sense of credibility as knowers and producers of knowledge. Attention is paid to how the cycle of shared reflection and adaptation inherent in the PAR approach re-characterised power relationships between staff and students. We discuss how moments of discomforting disequilibrium were catalytic in the redistribution of power across the group. We maintain that adapting a PAR approach aimed at contributing to the Scholarship of Teaching and Learning (SoTL), provides students with opportunities to develop their epistemic confidence. However, for this to happen, students and staff must be willing to work with disequilibrium which emerges as student-staff power dynamics are challenged.